Interventions for the eradication of meticillin-resistant Staphylococcus aureus (MRSA) in people with cystic fibrosis - Smyth, Alan R. (Wiley, 2015)
Background: Cystic fibrosis is an inherited recessive disorder of chloride transport that is characterised by recurrent and persistent pulmonary infections from resistant organisms that result in lung function deterioration and early mortality in sufferers. Meticillin-resistant Staphylococcus aureus (MRSA) has emerged as, not only an important infection in long-term hospitalised patients, but also as a potentially harmful pathogen in cystic fibrosis, and has been increasing steadily in prevalence internationally. Chronic pulmonary infection with MRSA is thought to confer cystic fibrosis patients with a worse overall clinical outcome and, in particular, result in an increased rate of decline in lung function. Clear guidance for the eradication of MRSA in cystic fibrosis, supported by robust evidence from good quality trials, is urgently needed. Objectives: To evaluate the effectiveness of treatment regimens designed to eradicate MRSA and to determine whether the eradication of MRSA confers better clinical and microbiological outcomes for people with cystic fibrosis. Search methods: Randomised and quasi-randomised controlled trials were identified by searching the Cochrane Cystic Fibrosis and Genetic Disorders Group’s Cystic Fibrosis Trials Register, PUBMED, MEDLINE, Embase, handsearching article reference lists and through contact with local and international experts in the field. Date of the last search of the Group’s Cystic Fibrosis Trials Register: 04 September 2014. Selection criteria: Randomised or quasi-randomised controlled trials comparing any combinations of topical, inhaled, oral or intravenous antimicrobials with the primary aim of eradicating MRSA compared with placebo, standard treatment or no treatment.